2011
DOI: 10.1097/tin.0b013e3182260d69
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perspectives About Dietary Maintenance in Type 2 Diabetes

Abstract: This investigation used a qualitative, open-ended semistructured interview guide to understand the perspectives of individuals with type 2 diabetes (n = 23) concerning factors necessary to maintain dietary changes. Five categories related to maintenance of diagnosis-related dietary changes emerged: self-discipline; understanding emotions; supportive relationships with family, friends, and health care providers; need for education; and strategies to maintain a healthy diet. While the small sample limits applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…Many authors describe self-discipline as a central intrapersonal challenge to diet modification [26][27][28][29][30][31][32] both for people who identify as socially marginalized [26][27][28]30,31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and nonmarginalized. 29,[53][54][55][56][57][58][59][60][61][62][63][64][65] Some authors explore the nature and experience of exercising self-control, but most concentrate on the challenges and enablers of self-discipline for those trying to modify their diets.…”
Section: Self-disciplinementioning
confidence: 99%
See 1 more Smart Citation
“…Many authors describe self-discipline as a central intrapersonal challenge to diet modification [26][27][28][29][30][31][32] both for people who identify as socially marginalized [26][27][28]30,31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and nonmarginalized. 29,[53][54][55][56][57][58][59][60][61][62][63][64][65] Some authors explore the nature and experience of exercising self-control, but most concentrate on the challenges and enablers of self-discipline for those trying to modify their diets.…”
Section: Self-disciplinementioning
confidence: 99%
“…Participants conceptualize self-discipline as something that can and should be controlled by the individual, 56,58,60,61,87 and something that exists in limited capacity, eroded by repeated temptations or difficult circumstances. Participants would activate self-discipline by avoiding tempting food and circumstances where unhealthy food is typically consumed.…”
Section: Barrier Key Pointsmentioning
confidence: 99%
“…The fact that age and marital status led to an increase in adherence of this factor, could be explained by the fact that as people grow older, they are also more likely to marry, thus their effect could be the same. To support this finding, one study revealed that marital status and or having a family member with knowledge about diabetes care influenced its management [17,25] and that if a family member had knowledge then they were supportive to diabetes management leading to increased adherence to treatment regimes. Marital status also led to an increase in adherence factor five (healthy diet promotion), whose focus was on maintaining healthy eating through vegetable consumption.…”
Section: Discussionmentioning
confidence: 97%
“…Жене Иранског порекла су изјавиле да немају довољно вемена за припрему здраве хране, иако им је она неопходна због дијабетеса 19 . Gutschall 20 је у свом истраживању изнела да недостатак рутине у планирању припреме хране доприноси неправилној исхрани и да би увођење реда у планирање значајно олакшало спровођење дијете.Такође је истакла да стрес утиче наизбегавање правилне дијате, што се увидело и у овом истраживању 20 . Веома често се пацијенти са дијабетесом не придржавају прописане дијете јер немају новца да купе потребне намирнице.…”
Section: дискусијаunclassified
“…У негативном смислу су утицали други дијабетичари, који се не придржавају пропи-сане дијете или особе које негирају озбиљ-ност шећерне болести. Многе студије су по-казале значај друштвеног утицаја на однос пацијената према исхрани, као и на недоста-так мотивације [16][17][18][19][20][21] . И карактер пацијената јако утиче на то да ли ће пацијент више да истраје у спровођењу дијете, или пак да поклекне под утицајем окружења или већ стечених старих навика.…”
Section: дискусијаunclassified